METHODOLOGICAL APPROACHES TO ASSESSING THE QUALITIES OF A LEADER THAT CONTRIBUTE TO INCREASING THE COMPETITIVE ADVANTAGES OF PHARMACY ORGANIZATIONS - Андрей Георгиевич Петров; Ольга Владимировна Хорошилова; Виктор Андреевич Семенихин; Сергей Николаевич Филимонов; Наталья Степановна Черных (Медицина в Кузбассе, 2025)
The modern concept of successful management of a pharmacy organization as a whole is focused on such values as the effectiveness of realizing the labor and personal potential of the head and the specialists working in it. Increasing the competitive position of pharmacy organizations requires their managers to have such abilities and personal qualities as: the ability to manage themselves and influence others, solve various kinds of problems and motivate subordinates, show their creative approaches to managing the professional activities of specialists and the formation of a favorable socio-psychological climate in the team.